Determinants of lender choice and banking strategy for Kansas farmers - Brewer, Brady (Kansas State University, 2012)
The objectives of this thesis are to examine the banking strategy of Kansas farmers and to analyze the determinants of lender choice among Kansas farmers. To meet these objectives, econometric analysis was used to examine the financial characteristics of the farm that affect the number of banking relationships and the probability a farmer has a loan with a respective lender. The financial characteristics include variables representing the solvency, liquidity, and profitability of the farm. To analyze banking strategy, a poisson model was estimated to determine how the financial characteristics of the farm affect the number of banking relationships used by the farmer. The solvency, liquidity, and profitability of a farmer was analyzed to examine how these measures affect how many banking relationships the respective farmer has. Additionally, a panel data fixed effects model was used to analyze how the number of banking relationships affects the net farm income of the farm. To analyze the determinants of lender choice for Kansas farmers, six probit models were used to determine how farm and financial characteristics, including dollar amount of inventory for certain assets and dollar amount of loans, affect the probabililty the farmer has a loan with the respective lender. A Heckman selection model was used to further analyze the dollar amount of loans a farmer has with a respective lender using information from the probit models. Results of the study show that the higher the debt to asset ratio the farmer has, the more banking relationships the respective farmer has. It was also found that the amount of inventory for certain asset classifications, dollar amount loans, and the financial characteristics affect the lender the farmer chooses to use.
Keywords: Agricultural finance; Agricultural lenders; Banking strategy; Agriculture, General (0473); Banking (0770); Economics, Agricultural (0503)